PENGARUH KUALITAS KOMUNIKASI INTERPERSONAL, MOTIVASI BERPRESTASI DAN KREATIVITAS TERHADAP PERILAKU PRODUKTIF ANGGOTA (Studi pada Kelompok Swadaya Badan Keswadayaan Masyarakat Program PNPM Mandiri Perkotaan di Kecamatan Ujungberung Kota Bandung) - MUHAMMAD IRFAN HILMI (Jurnal Pendidikan Luar Sekolah, 2016)
MUHAMMAD IRFAN HILMI, The Influence of The Interpersonal Communication Quality, Achievement Motivation and Creativity to Productive Behavior (Study On Self-Help Groups Community Self-Reliance Agency (BKM) PNPM Mandiri Perkotaan Program in Ujungberung District of Bandung).This study investigates the influence of the quality of interpersonal communication, achievement motivation, and creativity to productive behavior KSM members of the Community Self-Reliance Agency Program PNPM Mandiri Perkotaan in Ujungberung District of Bandung. The hypothesis proposed is a significant difference between: the quality of interpersonal communication to productive behavior, achievement motivation to productive behavior, creativity to productive behavior, the quality of interpersonal communication, achievement motivation and creativity together to productive behavior members of KSM.Literature review in this study include concepts such productive behavior, the concept of quality of interpersonal communication, the concept of achievement motivation, the concept of creativity, and the concept of community empowerment.The method used is quantitative approach with a correlation method is to determine the degree of influence between independent variable (X) to the dependent variable (Y). The study population was a member of KSM in BKM Ujungberung District of Bandung. The sampling technique using cluster sampling technique to obtain samples of this study as many as 35 people. Based on the results of the study found that; 1) influence the quality of interpersonal communication to productive behavior KSM Members showed positive price of 0.505 are is included in the category of relationship that is strong enough to influence the contribution of 25.5%; 2) the influence of achievement motivation to productive behavior KSM members showed positive price of 0.397 are included in the category of low relation to influence the effect by 15.8%; 3) the influence of creativity to productive behavior KSM members showed positive price of 0.517 are included in the category of relationship that is strong enough to influence the contribution of 26.7%; 4) the influence of the quality of interpersonal communication, achievement motivation and creativity simultaneously to productive behavior of members showed positive price of 0.714 are included in the category of very strong relationships with the contribution of the effect of 51%. From the results of this study indicate the quality of interpersonal communication, achievement motivation and creativity has a very strong contribution to the increase of productive behavior KSM members, so that all four proposed hypothesis is accepted.Keywords: Quality of Interpersonal Communication, Achievement Motivation, Creativity, Productive Behaviors.